Field report, Iowa, spring 1999, Mike Dooley - Dooley, Michael C.et al (1999)
An annotated list of birds sighted by Mike Dooley. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed